Despite antiretroviral therapy (ART) rollout, most cases of tuberculosis among people with HIV in Adama, Ethiopia, occur before ART initiation - Patrik Bristedt; Meseker Fentie; Per Björkman; Anton Reepalu (Global Health Action)
Introduction Although antiretroviral therapy (ART) leads to reduced tuberculosis (TB) incidence in people with HIV (PWH), ART recipients remain at higher risk of TB compared to HIV-seronegative people. With accelerated ART rollout in sub-Saharan Africa, increasing proportions of TB cases among PWH in people receiving long-term ART have been reported. Objective To determine TB notifications among PWH by ART status in a mainly urban uptake area in Ethiopia during an 8-year period in connection to the introduction of the ‘test-and-treat’ strategy for HIV. Methods PWH were identified from registers at health facilities providing ART in Adama and surrounding areas, Ethiopia 2015–2022. Annual TB notifications were compared over time. PWH within TB were categorized by ART status at the time of TB diagnosis (pre-ART TB: TB diagnosed before or ≤6 months after starting ART; ART-associated TB: TB diagnosed >6 months after starting ART). Results Among a total of 8,926 PWH, 993 had been diagnosed with TB (11.1%); mean age 40.0 years [SD 11.8], 53.5% were men). Throughout the study period, most TB cases had been notified before ART initiation (617/993; 62.1%). ART-associated TB cases constituted a mean of 37.4% (range 23.8%–44.2%) of all TB cases among PWH annually. Median time from ART initiation to TB diagnosis among ART-associated TB was 6.0 years. Conclusion TB notifications among PWH in this area did not decrease 2015–2022, implying persistently high risk of TB among PWH in this setting. Most TB cases occurred in ART-naïve persons, illustrating late HIV diagnosis in this population.